2000
DOI: 10.1099/0022-1317-81-8-2111
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the complete genome sequence of black queen-cell virus, a picorna-like virus of honey bees

Abstract: A virus with picorna-like biophysical properties was isolated from South African honey bees. On the basis of serology, it was identified as an isolate of black queen-cell virus (BQCV). Nucleotide sequence analysis revealed an 8550 nt polyadenylated genome containing two large ORFs. The 5h-proximal ORF (ORF 1) represented 4968 nt while the 3h-proximal ORF (ORF 2) represented 2562 nt. The ORFs were separated by a 208 nt intergenic region and were flanked by a 657 nt 5h-untranslated region and a 155 nt 3h-untrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(81 citation statements)
references
References 20 publications
3
77
0
1
Order By: Relevance
“…BQCV was present throughout the year and was the most prevalent virus detected. BQCV has previously been reported in South Africa (Allen and Ball, 1996;Davison et al, 1999;Leat et al, 2000) and more recently in Uganda (Kajobe et al, 2010).…”
Section: Discussionmentioning
confidence: 81%
“…BQCV was present throughout the year and was the most prevalent virus detected. BQCV has previously been reported in South Africa (Allen and Ball, 1996;Davison et al, 1999;Leat et al, 2000) and more recently in Uganda (Kajobe et al, 2010).…”
Section: Discussionmentioning
confidence: 81%
“…The symptoms and causes are not clear. Allen and Ball (1996) reported that at least 18 viruses infect A. mellifera, which can be present in all bee development stages: egg, larva, pupae, and adult (Chen et al, 2006 (Tentcheva et al, 2004;Yooa et al, 2012) and their complete genome sequences have been reported (Ghosh et al, 1999;Govan et al, 2000;Leat et al, 2000;Chen et al, 2004a;Fujiyuki et al, 2004;Maori et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Internal ribosome entry is a mode of translation initiation+ It is thought that an internal sequence element of mRNA recruits ribosomes onto an upstream region of the coding sequence, and therefore translation occurs independently of the 59 cap+ The RNA element that is responsible for ribosome entry is called the internal ribosome entry site (IRES)+ The first IRES elements were found in picornaviruses (Jang et al+, 1988;Pelletier & Sonenberg, 1988)+ Then others were found in several viral and cellular mRNAs, such as hepatitis C virus (Tsukiyama-Kohara et al+, 1992), cowpea mosaic virus (Thomas et al+, 1991), immunoglobulin heavy chain-binding protein (Macejak & Sarnow, 1991), and fibroblast growth factor 2 (Vagner et al+, 1995)+ For the IRES elements in cellular mRNA, a short nucleotide segment complementary to the 18S rRNA sequence has functional importance (Chappell et al+, 2000)+ In the viral IRES elements, the secondary and tertiary structure in the IRES has critical roles for translation initiation+ Three types of viral IRES elements are well characterized: those of the entero/rhinovirus, cardio/ aphthovirus, and hepatitis C virus groups+ These characterized IRES elements contain several stem-loop structures, and there are possible tertiary structure interactions between loops and bulges+ Within each group, the secondary structure is conserved, but there is almost no conservation between the groups (reviewed in Jackson & Kaminski, 1995;Lemon & Honda, 1997;Stewart & Semler, 1997)+ Cricket paralysis-like viruses (CrPV-like viruses) are a group of positive-stranded RNA viruses that infect insects+ These viruses are morphologically similar to picornaviruses; however, recently reported genome sequences have revealed that CrPV-like viruses have two open reading frames (ORFs), unlike picornaviruses+ To date, the genome sequences of seven CrPV-like viruses have been reported: Drosophila C virus (DCV; Johnson & Christian, 1998), Rhopalosiphum padi virus (RhPV; Moon et al+, 1998), Plautia stali intestine virus (PSIV; Sasaki et al+, 1998), himetobi P virus (HiPV; Nakashima et al+, 1999), Triatoma virus (TrV; Czibener et al+, 2000), cricket paralysis virus (CrPV; Wilson et al+, 2000a), and black queen-cell virus (BQCV; Leat et al+, 2000)+ The first ORF encodes a nonstructural protein precursor and the precursor is produced by IRESmediated translation (Wilson et al+, 2000a)+ The second ORF encodes a capsid protein precursor, and this precursor is also produced by IRES-mediated translation Domier et al+, 2000;…”
Section: Introductionmentioning
confidence: 99%